PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR PENJAS (STUDI PADA KELAS VIII SMP NEGERI 1 RENGEL TUBAN) - FAHRUDDIN, M. (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The objectives of this study are (1) to find whether the application of CTL method gives an influence on the result of studying physical education or not (2) to find how far the application of CTL method can give an influence on the result of the study after studying physical education. The object of this study are the eighth graders of Junior High School 1 Rengel Tuban for about 63 students. This study is conducted in the form of experimental research. While to collect data, the researcher conducted a test by asking the students to dribble a ball then take the results of pre-test and post-test. The result of this study can be concluded as follows: (1) whether the application of CTL method gives an influence on the result of studying physical education or not. The result of the calculation is collected by using Uji-T, it is found that the result of the t-hitung is 7,92, by making a correlation using taraf α=5% and N=63, it is found that the results of T-tabel is 2,000. From the analysis, it is found that T-hitung>T-tabel is 7,92>2,000. (2) the application of CTL method can increase the result of the study for about 15%. Based on the analysis, the hypothesis that says “there is a significant difference on the result of the study of physical education after the application of CTL method” can be accepted. It means that the CTL method can be an effective way to be applied in studying physical education because it can gives a significant difference in the result of the study of physical education for the eighth graders of Junior High School 1 Rengel Tuban. Keywords : Physical Education, Contextual Teaching and Learning (CTL) method.